2006
DOI: 10.1038/sj.onc.1209682
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of RhoA and RhoC characterizes the EMT and identifies RhoC as a prognostic marker of colon carcinoma

Abstract: Understanding how RhoC expression and activation are regulated is essential for deciphering its contribution to tumorigenesis. Here, we report that RhoC expression and activation are induced by the epithelial to mesenchymal transition (EMT) of colon carcinoma. Using LIM 1863 colon cancer cells, RhoC protein expression and subsequent activation were detected coincident with the loss of E-cadherin and acquisition of mesenchymal characteristics. Several Ets-1 binding sites were identified in the RhoC promoter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 27 publications
6
99
1
2
Order By: Relevance
“…A similar result was reported in breast carcinoma SUM-159 cell line, which revealed a compensatory relationship between RhoA and RhoC (27). As two Rho isoforms, RhoA and RhoC, share high sequence similarity, it is possible that they share similar feedback regulation or signaling pathway, which resulted in this compensation (28).…”
Section: Discussionsupporting
confidence: 64%
“…A similar result was reported in breast carcinoma SUM-159 cell line, which revealed a compensatory relationship between RhoA and RhoC (27). As two Rho isoforms, RhoA and RhoC, share high sequence similarity, it is possible that they share similar feedback regulation or signaling pathway, which resulted in this compensation (28).…”
Section: Discussionsupporting
confidence: 64%
“…The authors also observed that inhibition of RhoA gene expression increased the invasive capacity of the MCF-7 cells. Analogous effects were observed in colon cancer (6). Taken together, the findings of previous studies and the present study, indicate that knockdown of the RhoC gene may inhibit the TGF-β1-induced invasiveness of SiHa cells.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, EMT is characterized by alterations in the expression of a series of biomarkers, in particular, reduced E-cadherin and increased Vimentin expression levels. Ras homolog gene family, member C guanosine triphosphatase (RhoC GTPase) is an important member of the Rho-GTPase family, which regulates actin cytoskeleton reorganization during cellular motility, and actively participates in the EMT process (4)(5)(6). However, the role of RhoC in the process of EMT has remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These GTPases have been implicated in the progression of tumors from a broad range of cellular origins, and analyses at both the RNA and protein level have correlated their increased expression with tumor progression. Several Rho GTPases have been shown to regulate diverse signal transduction pathways and are involved in a variety of biological processes, including cell morphology, motility, proliferation, and apoptosis [11][12][13] . It has been known that gastric carcinogenesis is a multistep process with morphological progression involving multiple genetic and epigenetic events.…”
Section: Discussionmentioning
confidence: 99%